Basic research Environmental toxin 4-nonylphenol and autoimmune diseases: using DNA microarray to examine genetic markers of cytokine expression - Kim, Celline; Cadet, Patrick (Archives of Medical Science, 2010)
Introduction: Adverse progression of autoimmune diseases is linked to the dysregulation of cytokines. In this regard we investigated the role of 4-nonylphenol (4-NP), as a potential contributing factor in the development of immune diseases and compared it to estrogens actions since 4-NP may work via estrogen processes. Material and methods: The study made cytokine level expression changes in U937 cells by microarray technology coupled to RT PCR as a validating technique. Results: It was determined that 4-NP significantly up-regulated proinflammatory cytokine expression (toll-like-receptor [TLR]-6, TLR-10, interleukin [IL]-1, IL-5, IL-6, IL-17C, IL-23A, IL-8RB, IL-receptor-associated-kinase [IRAK-2], tumor-necrosis-factor-receptor [TNFR]-5, and TNFR-10). Estrogen caused insignificant increases but the changes parralelled that of 4-NP. Simultaneously, 4-NP down-regulated the expression of anti-inflammatory cytokines (IL-4 and IL-10), while estrogen up-regulated them. Conclusions: 4-Nonylphenol may initiate its toxic effects and pose a risk to autoimmunity-prone individuals by eliciting effects up to 4 times more potent than estrogen. Overall, exposure to 4-NP may contribute to autoimmune susceptibility and/or exacerbate existing autoimmune conditions by dysregulating normal expression of cytokines.